Nortriptyline in knee osteoarthritis (NortIKA Study): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Hudson, Ben; Williman, Jonathan; Stamp, Lisa; Alchin, John; Hooper, Gary; Mangin, Dee; Thompson, Bronwyn; Toop, Les
Abstract Background Osteoarthritis (OA) is a common cause of pain and disability. Currently available analgesics are often insufficiently effective or have unacceptable adverse effects. Tricyclic antidepressants may offer a useful centrally-acting analgesic. Nortriptyline is a readily-available, cheap and comparatively well-tolerated tricyclic antidepressant. Methods/Design We will conduct a parallel group, two-arm, participant and investigator-blinded, randomised controlled superiority trial comparing nortriptyline with placebo. Two hundred participants with primary knee OA will be enrolled. Participants will take study medication for 14 weeks. The primary outcome is difference between treatment arms in mean pain score measured on the Western Ontario and McMaster Universities (WOMAC) pain scale at 14 weeks. Discussion This protocol describes the first randomised controlled trial of a tricyclic antidepressant in the treatment of OA. The results of the study may have significant implications for the management of this common and painful condition. Trial registration The trial was registered with the Australian New Zealand Clinical Trials Registry on 27 June 2014. The trial registration number is:ACTRN12614000683639 .